Зимостійкість та морозостійкість сортів ґрунтопокривних троянд, інтродукованих до Національного ботанічного саду імені М.М. Гришка НАН України - Boiko, R.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Objective – to evaluate the winter resistance and frost resistance of 20 cultivars of groundcover roses from the collection of M.M. Gryshko National Botanical Garden of National Academy of Sciences of Ukraine (NBG). Material and methods. The subject of research – 20 cultivars of roses of the garden group “groundcover” from the collection of NBG. Field research on winter resistance was conducted in 2012–2017 in NBG according to the method of N.K. Vekhov (1957) with supplements of M.V. Besschotnova (1975). Frost resistance was investigated by the laboratory method of direct freezing of shoots in 2014 in the laboratory of the Institute of Horticulture of the National Academy of Agrarian Sciences of Ukraine using methodology “Laboratory and field methods for determining the frost resistance of fruit trees and crops” (2013). Results. The results of studying of the winter resistance (field method) are confirmed by the results of studying of frost resistance (laboratory method). The method of direct freezing of shoots has the advantages: it identifies the potential stability of the cultivar, and it can be used as an express method. Conclusions. The investigated cultivars of groundcover roses have varying degrees of winter resistance and frost resistance. 15 cultivars, which are the most winterresistant and frostresistant (potentially resistant to «critical» temperatures), we recommended for using in landscaping in the Right-Bank of Forest-Steppe of Ukraine.